A Two-level GREG Estimator for Consistent Estimation in Household Surveys - Anne Konrad; Jan Pablo Burgard; Ralf Münnich (International Statistical Review, 2021)
Household surveys provide information on both person-level and household-level characteristics. To ensure consistent estimates between both levels, statistical offices often use integrated weights that are equal for all persons within a household and the household itself. However, these integrated weights ignore the individual patterns of the persons, and the heterogeneity within a household is no longer reflected. As an alternative to integrated weighting, we propose a two-level generalised regression estimator that is capable of both ensuring consistent person and household estimates and allowing for different weights for persons within a household. A Monte Carlo simulation supports the superiority of our two-level generalised regression estimator compared with integrated weighting.
Keywords: 519; Integrated weighting; household surveys; generalised regression estimator; calibration; consistent estimation